SISTEM PAKAR PENDETEKSI KERUSAKAN PADA AUTO MOBIL - Akik Hidayat; Cucu Tohir (LPPM STMIK DCI, 2014)
Damage is an abnormal and unnatural state of the auto component parts car or all that causes discomfort, dysfunction or difficulty in terms of its use in the streets. So to fix (repair) the damage, people used to consult with a mechanic or technician skilled in the art. now it is very frequent and common in various types of vehicles in particularthe type of auto vehicle car. Damage can occur due to several factors including usage and maintenance factors that are not in accordance with the rules, resulting in auto vehicle car can be damaged either from minor damage to a very severe damage.The main discussion in this research is to design and manufacture of Damage Detection Expert System On Auto Car. The development of this expert system using the method for selecting the symptoms of damage which in turn is processed to become an information form of the cause of the damage until the solution to solve the problem of damage to the auto car. This expert system program materials adopted from the knowledge of an expert interview process, both automotive and source book or source module.The purpose of this software is to create an expert system used for the Detection of Damage At Auto Mobil early in order to do prevention early and minimize damage to the vehicle type Cars Auto harm caused by the prediction analysis of the repairs and to make it easier for owners and mechanics to perform maintenance and repairs. This expert system development using Borland Delphi 7.0 with Paradox database using a database 7.